Influence of lipid composition on the oral bioavailability of cinnarizine sub‐microemulsions. Issue 3 (20th July 2016) - Chen, Yinrong; Li, Xin; Wei, Xudan; Gou, Jingxin; Tang, Xing; He, Haibing; Xu, Hui
Abstract : The oral bioavailability of cinnarizine is usually limited by its poor solubility in the gastrointestinal tract. In this study, two kinds of cinnarizine sub‐microemulsions (SMEs) were prepared using medium (MCT) and long (LCT) chain triglycerides, respectively, and the effect of the lipid composition on the oral bioavailability of SMEs was investigated in terms of stability, in vitro lipolysis, in situ single‐pass intestinal perfusion, and in vivo pharmacokinetics. The SMEs increased cinnarizine stability in simulated gastrointestinal fluid and in vitro lipolysis products of LCT‐SMEs showed better cinnarizine solubilization capacity than that of MCT‐SMEs. In addition, the absorption rate (Ka) and the effective permeability coefficient ( P eff ) of LCT‐SMEs were significantly improved compared with MCT‐SMEs. The AUC0‐t value of LCT‐SMEs was 4132.6 ± 673.4 ng/mL · h, which was 1.94‐fold higher than that of the aqueous suspension. Moreover, the AUC0‐t value of LCT‐SMEs was also significantly greater than that of MCT‐SMEs (2490.7 ± 685.3 ng/mL · h), owing to the better drug solubilization capacity of the complex colloidal mixtures formed from digestion of LCT. Hence, LCT‐SMEs was successful in improving the oral bioavailability of cinnarizine and it was a superior drug vehicle for oral administration. Practical applications: Owing to poor solubility of cinnarizine in the gastrointestinal tract, its commercially available dosage forms including tablets and capsules exhibit low oral bioavailability. Here we propose SMEs to improve oral bioavailability of cinnarizine. In addition, the influence of lipid composition on the oral absorption of SMEs was investigated, and LCT‐SMEs significantly increased the oral bioavailability of cinnarizine compared with MCT‐SMEs. So, in this study we show that LCT‐SMEs is a promising drug vehicle for oral administration of cinnarizine. The colloidal structures generated from digested long chain triglycerides (LCT) have a better cinnarizine solubilisation ability than that generated from medium chain triglycerides (MCT) digestion, resulting in increased oral absorption for the LCT formulation compared with MCT. Abstract : The colloidal structures generated from digested long chain triglycerides (LCT) have a better cinnarizine solubilisation ability than that generated from medium chain triglycerides (MCT) digestion, resulting in increased oral absorption for the LCT formulation compared with MCT.